COVID-19 Delta Variant-of-Concern: A Real Concern for Pregnant Women With Gestational Diabetes Mellitus - Mamun, Md Mahfuz Al; Khan, Muhammad Riaz (Frontiers in Endocrinology, 2021)
The emergence of COVID-19 Delta variant-of-concern (VOC), a novel variant of SARS-CoV-2 has threatened the total health systems throughout the world. This highly contagious strain is spreading at higher exponential rate than any other variants of COVID-19 by infecting and subsequently killing hundreds of thousands of people globally. Amongst the most sensitive groups pregnant women are at high risk with increased hospitalization, pneumonia, requirement of respiratory support and admission to intensive care units during the Delta period. Pregnant people having gestational diabetes mellitus (GDM) are at increased chances of Delta VOC infection. GDM patients have nine-, and three-time more chances to be infected by Delta VOC than those pregnant women suffering from diabetes and cardiovascular diseases, and hypertension, respectively. Additionally, they are more vulnerable to Delta VOC infection than wildtype and Alpha COVID-19 VOC ones. Thus, this review critically sheds light over the current scenario of vulnerability of pregnant mothers, especially with GDM to Delta VOC infection.